THE PORTRAIT OF THE OLD LADY IN ERIC COBLE’S THE VELOCITY OF AUTUMN - Гайдаш, А.В. (Studia Philologica, 2016)
This article examines the portrayal of the elderly lady in the play “The Velocity of Autumn” (2014). Content analysis of the play suggests that the author modeled a charismatic ambivalent character who overcomes the oppression of the cross-generational bond. The female protagonist of the male playwright subverts disempowerment stereotypically associated with aging. Yet the oppression still takes place in the form of the language: there is a great deal of ageist self-stereotyping in the language of the elderly character. In terms of the play’s poetics the images of home and the tree in front of the window turn out as the projections of the character’s elderly self.